AIA guide to Chicago - Petersen, Laurie McGovern; Sinkevitch, Alice (University of Illinois Press, 2022)
"This is the fourth edition of the AIA Guide to Chicago, which is about 10-15 percent bigger than the last edition and includes a 32-page color insert. Chicago's architecture attracts visitors from around the globe. The fourth edition of the AIA Guide to Chicago is the best portable resource for exploring this most breathtaking and dynamic of cityscapes. The editors offer entries on new destinations like the Riverwalk, the St. Regis Chicago, and The 606 as well as updated descriptions of Willis Tower and other refreshed landmarks. Thirty-four maps and over 500 photos make it easy to find each of the almost 2000 featured sites. A special insert, new to this edition, showcases the variety of Chicago architecture with over 80 full-color images arranged chronologically. A comprehensive index organizes entries by name and architect. Sumptuously detailed and user friendly, the AIA Guide to Chicago encourages travelers and residents alike to explore the many diverse neighborhoods of one of the world's great architectural destinations"--